A Broadened Understanding of University Student Food Security: Undergraduate and Graduate Student Food Utilization and Access at a Big Ten University. Issue 1 (2nd January 2023) - Brandhorst, Sidney; Hodbod, Jennifer; Kaplowitz, Michael D.
ABSTRACT: Focusing on food access, existing college studies find rates of low or very low food security to range from 10–75%, with little understanding of variation among undergraduate and graduate students. A greater understanding of food security including access and utilization for both undergraduate and graduate students will help address its adverse effects on the health and academic outcomes of students. We evaluate food security at a large midwestern university, identifying characteristics related to both access and utilization. This approach allows for the identification of solutions tailored to undergraduate and graduate students living on- and off-campus who lack food security.